Monostotic Fibrous Dysplasia of the Rib: A Case Report - Asha Mahadevappa; Sapna Patel; Sunila Ravishankar; Gubbanna V. Manjunath (Case Reports in Orthopedics)
Fibrous dysplasia is a noninherited bone disease in which abnormal differentiation of osteoblasts leads to replacement of normal marrow and cancellous bone by immature bone with fibrous stroma. Monostotic fibrous dysplasia accounts for 28% in the ribs. It is often asymptomatic and incidentally detected on radiographs. As with many bone abnormalities, it can be superimposed by the formation of aneurysmal bone cysts. We report a case of a 70-year-old lady who presented with swelling on the chest wall of 20-ear duration and sudden increase in size for 8 months. Radiologically, X-ray and CT scan showed an expansible lesion of the medullary cavity with a ground-glass centre and thinning of cortex of the 5th rib. The resected lesion was a firm, well-defined solid, grey-white expansile mass replacing the medullary cavity. Histopathologically, benign fibrous spindle areas with disorganized irregular bony trabeculae were seen. Hemorrhagic spaces lined by osteoclast-like multinucleated giant cells were also noted. The diagnosis was fibrous dysplasia with aneurysmal bone cyst changes. Although fibrous dysplasia with aneurysmal bone cyst is rare, it should be taken into account in differential diagnosis of the rapidly growing solitary rib lesion.